2013
DOI: 10.21083/partnership.v8i1.2220
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Citation Management Systems: Which One Is Best?

Abstract: Librarians and researchers have long used citation management systems as research tools to help scholars organize their work, improve workflows, and ultimately save time. For many years, RefWorks has been the dominant citation management tool in many parts of Canada: the maturity of the product and its integration with many scholarly databases reassures users that it works well with these resources. However, a number of competitors now offer citation management systems that are as strong as RefWorks but offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Studies conducted by Evans et al (1990), Eichorn and Yankauer (1987) and Gupta et al (2005) found errors in major surgical journals in terms of citation and quotation. Steeleworthy and Dewan (2013) reviewed popular citation management systems, RefWorks, Zotero, WizFolio and Mendeley. To compare these software packages, they examined the import capabilities as well as the organizing, searching, annotating and sharing functions of these RMS.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted by Evans et al (1990), Eichorn and Yankauer (1987) and Gupta et al (2005) found errors in major surgical journals in terms of citation and quotation. Steeleworthy and Dewan (2013) reviewed popular citation management systems, RefWorks, Zotero, WizFolio and Mendeley. To compare these software packages, they examined the import capabilities as well as the organizing, searching, annotating and sharing functions of these RMS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several publications have been published comparing RMS packages using a set of criteria and features. Specific comparative studies of features have been performed by Dell’Orso (2010); Kessler and Van Ullen (2005); Steeleworthy and Dewan (2013).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, researchers have considered the benefits of using CMS (Basak, 2014, Garfield;Flanagan, & Fox 1989). Many articles provide direct comparisons between specific tools (Basak, 2014;Gilmour & Cobus-Kuo, 2011;Hensley, 2011;Steeleworthy & Dewan, 2013); others outline criteria for selecting the best software for a particular academic library (Butros & Taylor, 2011;Marino, 2012). Tramullas, Sánchez-Casabón, and Garrido-Picazo (2015) have conducted a literature review of such studies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…All of the products introduced substantive error. Steeleworthy and Dewan (2013) evaluated Zotero, WizFiolio, Mendeley and RefWorks for ease of use and functionality, including the ability to use the tools with mobile devices, but did not examine the accuracy of the four tools. They found considerable variation in the features offered by the citation managers and suggested that users select the appropriate tool based on their own needs.…”
Section: Literature Reviewmentioning
confidence: 99%